A guide to CCTV footage: How should it be used?. (2nd October 2021) - Green, Emma
Abstract : CCTV footage is part of subject access requests and an increasing number of queries from practice managers are related to such requests. Emma Green at Medical Protection looks at the relevant law and offers some tips